Pengaruh Moralitas Individu, Pengendalian Intern Dan Budaya Etis Organisasi Terhadap Kecenderungan Kecurangan Akuntansi - Dewi, Ni Komang Ayu Anita; Wirakusuma, Made Gede (E-Jurnal Akuntansi; Vol 29 No 1 (2019)DO - 10.24843/EJA.2019.v29.i01.p05, 2019)
Fraud can be seen from a deliberate form of policy and actions that aim to commit fraud or manipulation that can harm other parties. Fraud is an intentional act of fraud, generally in the form of a lie, plagiarism and theft. The purpose of this study was to examine the effect of individual morality, internal control, and organizational ethical culture on accounting fraud tendencies. The population used is 23 KSP in Tegallalang, Gianyar Regency. Methods of data collection using questionnaires, multiple linear regression analysis techniques used in. The results of the study show that individual morality, internal control and the ethical culture of the organization negatively affect accounting fraud tendencies. This means that the better the individual morality, internal control, and the application of organizational ethical culture in KSP, it will be able to reduce the level of accounting fraud tendencies that occur in KSP in Tegallalang District. Keywords : Individual morality; internal control; accounting fraud tendency; organizational ethical culture.